Tracer diffusion of globular proteins in concentrated protein solutions. - Muramatsu, N (1988)
The diffusion of tracer proteins at low concentration was measured in solutions containing "background" proteins at concentrations of up to 200 g/liter. The fractional reduction of the diffusion coefficient of tracer in the presence of a given weight/volume concentration of background species generally increases with increasing size of tracer species and with decreasing size of background species. The dependence of the diffusion constants of three out of four tracer species upon the concentrations of four background species is accounted for semiquantitatively by a simple hard particle model. Extrapolation of model calculations to higher background concentrations suggests that in solutions containing proteins at concentrations comparable to those found in biological fluid media, the diffusive transport of larger proteins and aggregates may be slower than in dilute solution by several orders of magnitude.